PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS JASA TRANSPORTASI ONLINE DALAM PERSPEKTIF EKONOMI ISLAM (Studi Empiris Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Lailatul Rofiqoh; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this study is to test The Effect of Service Quality on Online Transportation Services Loyalty in the Islamic Economy Perspective. Empirical studies on students of the Faculty of Economics and Business, Islamic University of Malang. Using online transportation at this time nowadays because  the existence of an online motorcycle taxi is more practical and easy, can order via the internet without having to go to an ojek base, trips can be tracked, the location of the driver when picking up can be known, the waiting time can be measured. The sampling technique used was purposive sampling, so the number of samples studied was 2984 x 15% = 448 students. Based on the results of this study that the quality of service (X) which consists of responsiveness, assurance, empathy, service reliability and physical services, has a significant effect on service loyalty with a significant value smaller than the value of 0.05. In the view of Islam, all human behavior must be in accordance with the orders of Allah SWT through the Al-Quran and Hadith. Islam teaches every business person to be professional that is able to work quickly and precisely so that he is mandated in his responsibilities.Keywords: Service Quality (Responsiveness, Assurance, Empathy, Service Reliability and Physical Services) Service Loyalty